Questioning Publicness Through Architectural Form: The Case of Atatürk Cultural Center - Dalgalı, Gökçe; Erkılıç, Neslinur Hızlı (Proceedings of the international conference of contemporary affairs in architecture and urbanism-ICCAUA, 2026)
This research explores the spatial production of publicness in Istanbul’s Beyoğlu district after 2010 urban transformations. The study examines how contemporary cultural nodes mediate the shifting perceptions of publicness amidst the tension between architectural intentions, institutional management, and everyday social practices. By utilizing Henri Lefebvre’s spatial triad (conceived, perceived, and lived space), the research interprets literature-derived publicness criteria through a qualitative lens. The Atatürk Cultural Center (AKM) is examined as a case study to uncover the relationship between its spatial configuration, management driven institutional publicness, and the lived reality of its users. By examining the multi layered thresholds of the node, the research explores how design choices and administrative protocols influence civic interaction and the realization of public life. This evaluation offers a critical perspective on contemporary cultural spaces in Istanbul, contributing to the academic discourse on the evolving and contested nature of urban publicness.